STUDIES INTAKE CALORIE WORKERS HAUL AT THE PORT OF TANJUNG PERAK AT SURABAYA BASED ON HEART RATE - ST. SALAMMIA, L.A (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2011)
Port of Tanjung Perak at Surabaya is second Indonesia’s biggest port that serves a variety of shipping inside or outside the cState so the bustle intensity of workers haul at this port is big enough then it is this which encourages us to measure the extent to which the condition of the calorie content is owned by the workers haul at that port impact on daily productivity and impact on healty. This research measuring calorie content is owned by the energy transport during activity or no activity at the time, because according to the physiology Ergonomics Science, people who do activities or not have already had a calorie standard that will be processed by the body into power even have been grouped by type of gender and age, The method of measuring calorie that is performed is measurement method based on heart rate at he time before do activities although during do activities with workers haul samples then converted into calorie unit with a base count of Basal Metabolism. In the research conducted for about 3 (three) months of the results obtained are an average of 1434.49 calories kcal, while the result owned only an average 1295.75 kcal. There is a shortage of calories in workers haul as much as 138.74 kcal, there for in the research do experiment by providing meals to increase calories as needed on average 10.88% every day and the menu is vary according to needs.